Rewrite the Future : How Indonesia's Education System Can Overcome the Losses from the COVID-19 Pandemic and Raise Learning Outcomes for All - Afkar, Rythia (World Bank, Washington, DC, 2021)
The policy note presents an updated estimate of learning loss due to COVID-19 (coronavirus) -related school closures in Indonesia, taking into account the Government of Indonesia~^!!^s mitigating measures. Our revised estimates show that school closures precipitated by the COVID-19 pandemic could result in a total loss of between 0.9 and 1.2 years of learning adjusted schooling and on average between 25 and 35 points on student’s PISA reading scores. The extent of learning loss is determined more by the effectiveness of distance learning than it is by the duration of school closure in the time period investigated. We identify a reduction of between 408 US dollars and 578 US dollars per student in future annual earnings equivalent to a present value loss in lifetime earnings for all students of between 253 and 359 billion US dollars, or 24 to 34 percent of 2020 GDP. To accelerate learning and to recover some of these losses in the short-term, schools and teachers can assess what each of their students has been able to learn while schools were closed and use differentiated plans to support each child to accelerate their learning. In the longer term, the Government can support the increased resilience of education service delivery to protect against future shocks from pandemics, climate change and other threats.